Guideline for the Development of Online Teaching and Learning Management to Meet the Demands of Students at Faculty of Management Science Bansomdejchaopraya Rajabhat University by Using the Kano Model - Wangplaicharoensuk, Wassaya; Pasunon, Prasopchai (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
This research uses the Kano model to study the characteristics of online teaching and learning management and ways to develop online teaching and learning management to meet the demands of students. The sample group consisted of 334 students from Bansomdetchaopraya Rajabhat University’s Faculty of Management Science. The tool used is a questionnaire on student needs, which contains 19 characteristics, both positive and negative, and the questionnaire data were analyzed using the Kano model to find the coefficient of satisfaction of students with online teaching and learning management. The survey and data analysis using the Kano model revealed that they were able to classify characteristics that affect the level of preference and impression of students. It can be divided into 2 groups: 1) attractive attributes that influence the impression or attraction of online learning, such as a teacher’s having already prepared and compiled the study material, and 2) necessary characteristics (expected features or must-haves) that affect satisfaction in online learning, consisting of: such as the university’s supporting the tools for online learning, earning points accumulated from work, a teacher’s readiness to teach online, and students’ readiness to study online.